Critical junctures: anarchistic leanings of current urbanization in Malaysia - Abdul Hadi Harman Shah,; Abdul Samad Hadi,; Shaharudin Idrus,; Ahmad Fariz Mohamed, (Environmental Management Society, Malaysia, 2010)
Development in Malaysia has reached a critical juncture where the expectations of end results and processes have drastically changed from the first time the New Economic Policy (NEP) outlined the future for the country. The focus on technocratic solutions to social problems, while still dominant, is increasingly being contested and supplemented by negotiated meanings of multiple symbols and evolving objectives, proposed at various entry points. Global market forces have changed the effectiveness of earlier centralized planning efforts and have opened up local development avenues that are not as dependent on the State as they were before. This has led to an increasingly anarchistic approach of direct development, a pattern that has caught many development planners by surprise. The urbanization phenomenon today is increasingly driven by individuals that take up risks and responding faster to the uncertain conditions of the market than the established bureacracy of development planning. These new agents of development are aware but no longer simply following the path set by the State, negotiating to capitalise on State-led programmes but with independent agendas. The current result is the creation of a syncretic rural-urban society with blurred physical and social boundaries. Using the everyday content of urbanization, the paper attempts to provide some insights into this dynamics of development that has permeated the rural-urban landscape of Malaysia. The Bernam-Linggi region which has experienced the changing whims of development and development planning is used as an example to illustrate the emergence of the urban through a coalescing of local drivers responding to the State and Market. The argument of the paper is articulated within a rhizomatic approach to the current urbanization phenomenon, emphasizing the bottom-up, lateral proliferation of individually determined views of development which resulted in the current urban-rural landscape of the the Bernam Linggi region in particular, and Malaysia in general. The paper also posits several implications for planning analysis and development programmes evaluation